Análise de uma história de armadilhas: a psicóloga judicial e o adolescente acolhido institucionalmente até a maioridade - Martins, Christina Tavares Mota (2014)
The issue of the institutionalization of children and adolescents until attaining legal adulthood is revealed within a context of scarce academic productions. The main objective of this paper was to investigate the meaning of the experience of attaining legal adulthood by the institutionalized subject who had no chance of being adopted and whose family had the parental rights ousted, and to intertwine this experience with the author‟s trajectory of eighteen years working as a judicial psychologist dealing with similar cases. Semi-structured interviews were directed to a seventeen-year-old female adolescent, on the verge of leaving the shelter, and to two of her colleagues, included in the research by demand of the first one. The psychoanalytic method, by means of interpretation, based the research, and fairy tales were utilized as metaphors in the analysis of this listening to the subject of the unconscious. The institutionalization until legal adulthood is experienced as being imprisoned in a place where the moment lived by the adolescent is denied, and also where the previous history of the subject is erased. The judicial psychologist, caught in the institutional webs and traps, is seen as a tormentor who, upon listening to the teenager, contributes to his/her institutionalization. The institutional sheltering of the adolescent whose family had the parental rights ousted signaled a recrudescence of the subject‟s helplessness and also the lack of a kind of work which created opportunities for the elaboration of losses.